SOCIAL INFLUENCE AND INTENTION TO PURSUE HIGHER EDUCATION AMONG ASNAF STUDENTS IN MALAYSIA - Ahmad Zulhusny Rozali; Wan Nurulasiah Wan Mustapa; Nur Zafirah Aqilah Zaiyadur Rashad; Wan Norsyafawati W. Muhamad Radzi; Nor’izah Ahmad; Muhammad Ahmar Ali (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study aims to examine the influence social influence (family and peer) factors on the intention to pursue higher education among Asnaf students in Perlis. It addresses the need to understand how social influences shape educational aspirations among students from low-income backgrounds. The study uses a quantitative approach based on Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze survey data collected from 418 Asnaf students in 27 listed secondary school in Perlis. The model tests two hypotheses relating to the impact of family influence and peer influence on students’ intention to further their education. The results show that family influence has a significant and positive effect on students’ intention to pursue higher education, while peer influence does not show a statistically meaningful impact. These findings highlight the critical role of family in shaping students’ educational decisions within this demographic group. This study contributes to the limited body of research focusing on Asnaf students and provides evidence on the different roles that family and peer relationships play in influencing their higher education intentions. The findings offer valuable insights for policymakers and educators to design support strategies that strengthen family engagement in educational planning.